2008
DOI: 10.1074/jbc.m707338200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Substrate and Oxygen Ligand Responsible for Effective O–O Bond Cleavage in Bovine Cytochrome P450 Steroid 21-Hydroxylase Proved by Raman Spectroscopy

Abstract: We investigated structural and functional properties of bovine cytochrome P450 steroid 21-hydroxylase (P450c21), which catalyzes hydroxylation at C-21 of progesterone and 17␣-hydroxyprogesterone. The uncoupled H 2 O 2 formation was higher in the hydroxylation of progesterone (26% of NADPH consumed) than that of 17␣-hydroxyprogesterone (15% of NADPH consumed), indicating that 17␣-hydroxyprogesterone can better facilitate the O-O bond scission. In relation to this, it is noted that the O-O stretching mode ( O-O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Finally, it is noted that the 347 cm −1 value observed for the ν(Fe-S) mode is at the low end of values obtained for other cytochromes P450, which range between ~353 down to 347 cm −1 . 29,32,49-52 As will be seen, this lower ν(Fe-S) has an impact on the ν(Fe-C) and ν(C-O) modes of the trans-axial Fe-C-O fragment (vide infra).…”
Section: Resultsmentioning
confidence: 90%
“…Finally, it is noted that the 347 cm −1 value observed for the ν(Fe-S) mode is at the low end of values obtained for other cytochromes P450, which range between ~353 down to 347 cm −1 . 29,32,49-52 As will be seen, this lower ν(Fe-S) has an impact on the ν(Fe-C) and ν(C-O) modes of the trans-axial Fe-C-O fragment (vide infra).…”
Section: Resultsmentioning
confidence: 90%
“…The involvement of the hydroxyl group of the substrate in proton delivery was reported for P450c21, P450 107A, and P450 158A2 (Nagano et al, 2005; Zhao et al, 2005; Tosha et al, 2008). P450c21 catalyzes the hydroxylation of progesterone and 17α-hydroxyprogesterone at C-21 position and the reaction is better coupled with 17α-hydroxyprogesterone by 11%.…”
Section: Introductionmentioning
confidence: 87%
“…P450c21 catalyzes the hydroxylation of progesterone and 17α-hydroxyprogesterone at C-21 position and the reaction is better coupled with 17α-hydroxyprogesterone by 11%. The studies of the vibrational mode of the oxyferrous P450c21 by Raman spectroscopy demonstrated that ν O-O is sensitive to the substrate; progesterone gave a single ν O-O band at 1137 cm −1 while 17α-hydroxyprogesterone split ν O-O into two bands at 1124 and 1138 cm −1 (Tosha et al, 2008). It was postulated that 17α-hydroxyprogesterone is hydrogen bonded to the iron-linked oxygen and participates in proton delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Substrate binding to P450s 102A1 [123], 19A1 (aromatase) [124], 2B4 [125], and 2D6 [126] has been studied with resonance Raman spectroscopy. Recently the differences between oxidation efficiency of two endogenous substrates of P450 21A1 (steroid 21-hydroxylase), progesterone and 17α-hydroxyprogesterone, have been explained with the aid of resonance Raman spectroscopy studies [127]. P450-substrate interactions have also been studied on self-assembled monolayer (SAM)-coated metal surfaces (silver and gold) by resonance Raman scattering spectroscopy [126, 128] where the sensitivity is increased via so called surface enhancement [129].…”
Section: Raman Spectroscopymentioning
confidence: 99%